THE ROLE OF FINANCIAL LITERACY IN ADVANCING ENTREPRENEURSHIP: EMERGING INSIGHTS FROM CHITRADURGA, KARNATAKA - K., Leelavathi; L., Ramesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Financial literacy is increasingly recognized as a cornerstone for empowering entrepreneurs, particularly in semi-urban regions where access to formal education and structured financial services may be limited. This study investigates the relationship between financial literacy and entrepreneurial success in Chitradurga, Karnataka, focusing on local small business practices, the barriers to accessing formal credit, and the adoption of digital payment systems. Utilizing a mixed-method approach, including surveys and interviews with both entrepreneurs and financial experts, the research provides insights into the challenges faced by local businesses and offers recommendations to enhance financial literacy and promote business sustainability. This paper argues for the integration of targeted financial education into regional development programs to foster sustainable business growth and economic resilience.